Gaia and Political Sociology: On the Legacy of Bruno Latour (1947-2022) - Gertenbach, Lars (Journal of Political Sociology, 2023)
If one had to discern a center of gravity in Bruno Latour’s voluminous and multi-layered work, one could find it in the question of the political. At first glance, this may seem unexpected. After all, it is only with his decidedly political texts since the turn of the millennium that many have become aware of the political dimension of his work. Yet, Latour’s most recent work leaves no doubt that there is no way around the topic of politics (anymore) in the discussion of his writings in general. Given the death of Bruno Latour on October 9, 2022, this genuinely political dimension of his work will be re-examined in the following. In doing so, I would like to address some strands of Latour’s political sociology while emphasizing that he is to be understood as a political sociologist through and through – and not just in passing.